Beyond blurred lines : rape culture in popular media - Phillips, Nickie D. (Lanham, Maryland : Rowman & Littlefield, 2017)
From its origins in academic discourse in the 1970s to our collective imagination today, the concept of "rape culture" has resonated in a variety of spheres, including television, gaming, comic book culture, and college campuses. Beyond Blurred Lines : Rape Culture in Popular Media traces ways that sexual violence is collectively processed, mediated, negotiated, and contested by exploring public reactions to high-profile incidents and rape narratives in popular culture. The concept of rape culture was initially embraced in popular media-- mass media, social media, and popular culture-- and contributed to a social understanding of sexual violence that mirrored feminist concerns about the persistence of rape myths and victim-blaming. However, it was later challenged by skeptics who framed the concept as a moral panic. Nickie D. Phillips documents how the conversation shifted from substantiating claims of a rape culture toward growing scrutiny of the prevalence of sexual assault on college campuses. This, in turn, renewed attention toward false allegations, and away from how college enforcement policies fail victims and endanger accused young men. Ultimately, Phillips successfully lends insight into how the debates around rape culture, including microaggressions, gendered harassment, and so-called political correctness, inform our collective imaginations and shape our attitudes toward criminal justice and policy responses to sexual violence. -- Back cover.
Acknowledgments -- Rape culture : the evolution of a concept -- The mainstreaming of rape culture -- "Hey TV stop raping women" -- Geek spaces : "pretty girls pretending to be geeks" -- Geek spaces : feminist interventions and "witch hunts" -- Rape culture on campus: "real men don't hurt women" -- Reconciling panic and policy -- Appendix -- Resources -- Index -- About the author.
Includes index.
Includes bibliographical references (pages 193-292) and index.
Keywords: Rape; Rape in mass media